Improving Students’ Understanding and Representational Fluency of Kinematics Through Learning Cycle 5E with Multi Representational Approach - Dianningrum, Magfira Cindy; Sufian, Enio Kang Mohd (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2025)
The use of various forms of representation is believed to help students understand the concept of kinematics better. This research aims to determine the increase in students' conceptual understanding and representational fluency in the kinematics of straight motion through Learning Cycle 5E with multi representational approach on 32 class XI students of State High Schools in Malang. Students' conceptual understanding is assessed with seventeen reasoned multiple choice questions, while representational fluency are assessed with five essay questions. Based on the results of the analysis, students' conceptual understanding and representation abilities increase through the learning carried out. Increased understanding of concepts based on testsN-gain namely 0.693, while the increase in students' representational fluency was 0.654.DOI: 10.17977/jps.v13i12025p020